انترنت الأشياء وتطبيقاتها في مجال الخدمات اللوجستية - محلوس, زكية; خلف, منى; بقاط, حنان (University of Eloued جامعة الوادي, 2022)
The research paper aims to identify the concept of the Internet of Things and its most important applications in the field of logistics, specifically what is related to foreign trade, an exploratory descriptive study to achieve the goal of the study. And we found that there are many applications of the Internet of Things in the field of logistics, especially in the supply chain, transportation, customs, ports and smart containers, which is expected to be reflected in an improvement in the logistics performance index in many countries, especially developed countries that are considered pioneers in the use of digital technology, in addition to increasing their investments. In the Internet of things related to logistics services, we also found that there is an increase in companies that use the Internet of things on the one hand, and an increase in companies that invest in logistics services on the other.
Internet of things and its applications in the field of logistics services
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: انترنات الأشياء، الخدمات اللوجستية، الموانئ الذكية، التجارة الخارجية; Internet of Things, Logistics services; Smart ports, Outside trade.